2022
DOI: 10.1007/s11356-022-18918-4
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene with hand sanitizer versus handwashing: what are the planetary health consequences?

Abstract: In order to reduce the transmission of pathogens, and COVID-19, WHO and NHS England recommend hand washing (HW) and/or the use of hand sanitizer (HS). The planetary health consequences of these different methods of hand hygiene have not been quantified. A comparative life cycle assessment (LCA) was carried out to compare the environmental impact of the UK population practising increased levels of hand hygiene during the COVID-19 pandemic for 1 year. Washing hands with soap and water was compared to using hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(14 reference statements)
0
6
0
Order By: Relevance
“… 151 Method of hand hygiene should also be considered, a study on surgical scrubbing in the UK found using alcohol-based hand gel could save approximately 930 000 L of water per year for an average UK hospital. 152 Recently, Duane et al 153 conducted a hand hygiene life cycle analysis and concluded that alcohol-based hand gel was more environmentally sustainable than handwashing with soap. However, it should be noted that this study compared the hand hygiene methods at population level use rather than within a hospital setting in which the alcohol gel might not be suitable for clinical use.…”
Section: Methodsmentioning
confidence: 99%
“… 151 Method of hand hygiene should also be considered, a study on surgical scrubbing in the UK found using alcohol-based hand gel could save approximately 930 000 L of water per year for an average UK hospital. 152 Recently, Duane et al 153 conducted a hand hygiene life cycle analysis and concluded that alcohol-based hand gel was more environmentally sustainable than handwashing with soap. However, it should be noted that this study compared the hand hygiene methods at population level use rather than within a hospital setting in which the alcohol gel might not be suitable for clinical use.…”
Section: Methodsmentioning
confidence: 99%
“…In endoscopy, full hand disinfection is not required and use of alcohol rubs instead of hand washing may be done when hands are not visibly soiled or in contact with potential spore-forming pathogens. 27,28 Both alcohol-based gels and petrochemical soaps are not environmentally safe as they contaminate water sources. 29 Use of natural and environment friendly products may be the way forward.…”
Section: Minimizing Water Wastagementioning
confidence: 99%
“…In comparison to soap, sanitizers are not effective against all types of germs (ex-against non virus agents and Clostridium difficile) and in case of dirty and greasy hands (Vermeil et al, 2019). A comparative life cycle assessment (LCA) of hand washing with soap (soap+water) and hand sanitizer (both ethanol and isopropanol based sanitizers) was carried out in UK to compare the environmental impact of increased levels of hand hygiene during the COVID-19 pandemic (Duane et al, 2022). The isopropanolbased hand sanitizer had the lowest environmental impact in 14 out of the 16 impact categories used in this study.…”
Section: Environment Conservation Journalmentioning
confidence: 99%
“…When comparing hand sanitizers to hand washing with soap and water, this study found that using isopropanol based hand sanitizer is better for planetary health. However, no method of hand hygiene was ideal; isopropanol had a greater fossil fuel resource use than ethanol based hand sanitizer (Ghafoor et al, 2021;Duane et al, 2022).…”
Section: Environment Conservation Journalmentioning
confidence: 99%